The Star, 11 September 2009 - Then, Stephen; Florence A. Samy; R.K. Shyamala; Fong, Loh Foon; Ling, Sharon (Star Publications (Malaysia) Berhad, 2009)
It has been confirmed that Penan girls and woman were raped and molested by timber com[any workers in Sarawak's Ulu Baram district.